PENGARUH PENGARUH KEADILAN PAJAK, KESADARAN WAJIB PAJAK, DAN TARIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DI KOTA MALANG : PENDAHULUAN - Pujo Gunarso Pujo Gunarso (STIE Madani Balikpapan, 2026)
Abstract This study aims to analyze the influence of tax fairness, compliance costs, and tax rates on individual taxpayer compliance in Malang City. The data analyzed were primary data, distributed through questionnaires in Malang City. This study is based on the Theory of Planned Behavior, which explains that compliance behavior is influenced by attitudes, subjective norms, and perceived behavioral control. The analysis tool used was IBM SPSS Statistics 22. The methods used were descriptive analysis, validity testing, reliability testing, classical assumption tests (normality test, multicollinearity test, and heteroscedasticity test), multiple regression analysis, and hypothesis testing (F test, t test, coefficient of determination test, and dominance test). Sampling used a simple random sampling technique with 98 respondents drawn from individual taxpayers in Malang. The results of this study indicate that tax fairness, compliance costs, and tax rates have a positive and significant effect on individual taxpayer compliance in Malang City. Keywords: Tax Fairness, Compliance Costs, E-tax system, Tax Rates, Tax Compliance